Optimization of REMS Program Compliance in a Large Academic Health System - Audrey B Kostrzewa (INNOVATIONS in Pharmacy, 2021)
Ensuring compliance with all applicable Risk Evaluation and Mitigation Strategies (REMS) programs within a health system is challenging. These FDA-mandated programs are numerous, unique, and ever-changing. Actions require several stakeholders and moving parts. In addition, the effectiveness and impact of these programs has been challenged and is not always clear, which hampers buy-in and therefore compliance.